ANALISIS BELANJA TIDAK LANGSUNG KABUPATEN/KOTA DI PROPINSI JAMBI TAHUN 2009-2014 - Mila Permata Sari (Program Studi Manajemen Pemerintahan dan Keuangan Daerah Fakultas Ekonomi dan Bisnis Universitas Jambi, 2020)
This study aims to identify and analyze the development of indirect spending in districts / cities in Jambi Province in 2009-2014. In addition, it is also used to determine and analyze the efficiency of indirect spending in terms of district / municipal efficiency in Jambi Province 2009-2014. The technical analysis used is qualitative and quantitative analysis, analysis of expenditure allocation on indirect spending development, analysis of spending performance in terms of efficiency. The development of district / municipal indirect spending in Jambi province in 2009-2014 was based on the annual average, namely the highest in Bungo district at 1.19% and the lowest in Tanjung Jabung Timur district at 0.11%. Based on the efficiency of district / municipal indirect spending in Jambi province in 2009-2014, the average target indirect expenditure from year to year has increased because from 2009-2014 all districts have been efficient from year to year in managing indirect expenditure. Districts / Cities in Jambi Province in Sungai Penuh City have been very effective from the efficiency of indirect spending.